Development of a 24-hour movement index: exploring acceptability among Canadian parents - Zhan, Jian Kun; Khan, Karim M.; Tremblay, Mark S.; Faulkner, Guy (Frontiers in Sports and Active Living, 2025)
BackgroundThe Canadian 24-Hour Movement Guidelines for Children and Youth were introduced in 2016. They offer recommendations on moderate-to-vigorous physical activity, light physical activity, sedentary behaviour, and sleep in a typical 24-hour period to achieve optimal health outcomes. However, a lack of awareness and knowledge about the guidelines among children and parents is a concerning public health issue and may contribute to the low guideline adherence of Canadian children. A “Movement Index” app is planned to help parents track their children's movement behaviours through manual data entry and/or a wearable device. The Movement Index would also demonstrate to parents how the combination of their children's movement behaviours, such as a change in time reallocation, may be associated with different health outcomes. Using the Theoretical Framework of Acceptability, the objectives of this study were to (1) explore interest in, and acceptability of, the proposed Movement Index, and (2) identify potential refinements in developing the app.MethodsIndividual semi-structured interviews were conducted over Zoom with 22 parents of children aged 5–11 years from across Canada. Interview data were analyzed with thematic analysis using a constant comparative method.ResultsResults suggest that the Movement Index is acceptable on two constructs (perceived effectiveness, intervention coherence), mostly acceptable on two (affective attitude, ethicality), and has mixed acceptability for the remaining three (burden, opportunity cost, self-efficacy).DiscussionOn balance, the Movement Index was found to be acceptable, and the project should proceed with several caveats that need to be addressed regarding accessibility and ethical concerns. Future work is required to develop and pilot the Movement Index before further re-examining its acceptability and usability.